![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. x(x-2)+x-2=0
=> (x-2).(x+1)=0
=> x-2=0 hoặc x+1=0
=> x=2 hoặc x=-1
b. 5x(x-3)-x+3=0
=> 5x(x-3)-(x-3)=0
=> (x-3).(5x-1)=0
=> x-3=0 hoặc 5x-1=0
=> x=3 hoặc x=1/5
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x\left(x-2\right)+x-2=0\)
<=> \(\left(x-2\right)\left(x+1\right)=0\)
<=> \(\orbr{\begin{cases}x-2=0\\x+1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=2\\x=-1\end{cases}}\)
Vậy...
b) \(5x\left(x-3\right)-x+3=0\)
<=> \(\left(x-3\right)\left(5x-1\right)=0\)
<=> \(\orbr{\begin{cases}x-3=0\\5x-1=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=3\\x=\frac{1}{5}\end{cases}}\)
Vậy...
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a)\)\(x^3-x^2-x+1=0\)
\(\Leftrightarrow\)\(x^2\left(x-1\right)-\left(x-1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x^2-1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)\left(x-1\right)\left(x+1\right)=0\)
\(\Leftrightarrow\)\(\left(x-1\right)^2\left(x+1\right)=0\)
\(\Leftrightarrow\)\(\orbr{\begin{cases}\left(x-1\right)^2=0\\x+1=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=-1\end{cases}}}\)
Vậy \(x=1\) hoặc \(x=-1\)
Chúc bạn học tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
b) (x-3)2-(x-3)(x+3)=0
<=>(x-3)[(x-3)-(x+3)]=0
<=>(x-3)[x-3-x-3]=0
<=>(x-3)*(-6)=0
<=>x=3
a) (x-2)(x+2)-7=(x-1)2
<=>x2-4-7=x2-2x+1
<=>x2-11-x2+2x-1=0
<=>(x2-x2)+2x-11-1=0
<=>2x-12=0
<=>2x=12
<=>x=6
Bài giải
\(\left(x-3\right)2-\left(x-3\right)\left(x+3\right)=0\)
\(\left(x-3\right)\left(x+3-2\right)=0\)
\(\left(x-3\right)\left(x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-3=0\\x+1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=-1\end{cases}}\)
\(\Rightarrow\text{ }x\in\left\{3\text{ ; }-1\right\}\)
\(\left(x-3\right).2-\left(x-3\right)\left(x+3\right)=0\Leftrightarrow\left(x-3\right)\left[2-\left(x+3\right)\right]=0\)
\(\Leftrightarrow\left(x-3\right)\left(2-x-3\right)=0\Leftrightarrow\left(x-3\right)\left[\left(-1\right)-x\right]\). Xét 2 trường hợp
Xét 2 trường hợp. \(TH1:x-3=0\Leftrightarrow x=0+3=3\)
\(TH2:\left(-1\right)-x=0\Leftrightarrow x=\left(-1\right)-0=-1\). Vậy \(x\in\left\{-1;3\right\}\)